2000
DOI: 10.1118/1.598966
|View full text |Cite
|
Sign up to set email alerts
|

A systematic evaluation of air cavity dose perturbation in megavoltage x‐ray beams

Abstract: The EGS4 Monte Carlo radiation transport code was used to systematically study the dose perturbation near planar and cylindrical air cavities in a water medium irradiated by megavoltage x-ray beams. The variables of the problem included x-ray energy, cavity shape and dimension, and depth of the cavity in water. The Monte Carlo code was initially validated against published measurements and its results were found to agree within 2% with the published measurements. The study results indicate that the dose pertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 25 publications
3
40
0
Order By: Relevance
“…A re-build up region occurs as electrons are once again generated in water-equivalent material. Allen et al reported that the dose reduction near an air cavity was greater for smaller field size, higher energy, larger air cavity size, and shallower depth in water where the air cavity was situated [10]. Klein et al results showed that following a 2.0 cm wide air channel for a 4 MV X-ray with 4 × 4 cm 2 field, there was an 11% under dose at the distal interface, while a 2.0 cm cubic cavity yielded only a 3% loss [4].…”
Section: Discussionmentioning
confidence: 99%
“…A re-build up region occurs as electrons are once again generated in water-equivalent material. Allen et al reported that the dose reduction near an air cavity was greater for smaller field size, higher energy, larger air cavity size, and shallower depth in water where the air cavity was situated [10]. Klein et al results showed that following a 2.0 cm wide air channel for a 4 MV X-ray with 4 × 4 cm 2 field, there was an 11% under dose at the distal interface, while a 2.0 cm cubic cavity yielded only a 3% loss [4].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the under dosing that gives rise to the skin-sparing effect could reduce the dose delivered to the rectal wall during treatment of prostate cancer, as reported by Holmes et al (1) .…”
Section: Introductionmentioning
confidence: 70%
“…In addition, about the measurement in phantom C, the dose reduction is higher than the measurement in phantom B, because the location of measurement is in the low-density area [4] [15]. The phenomena might be caused by the target mass attenuation which might involve in the measurements.…”
Section: Figure 2 Discrepancies For All Phantom Measurementmentioning
confidence: 99%
“…In fact, human body consists of materials having different densities such as lungs, soft tissues and bones which may represent inhomogeneity condition. Hence, the procedures of dose verification in the protocol might not fully represent the dose verification for human body (patients) and might cause a dose perturbation due to the inhomogeneity issues [4]. Moreover, the dose perturbation due to inhomogeneity issues might be more complex due to the use of small field technique for treating small volume targets.…”
Section: Introductionmentioning
confidence: 99%